Extraintestinal oxyuriasis - report of three cases and review of literature - Ondič, Ondrej; Neubauer, Ludvík; Sosna, Bohuslav (Ceskoslovenska patologie, 2014)
Extraintestinal oxyuriasis, in our experience with three affected women of fertile age, presented itself as a solitary fibrotic nodular lesion, with a varying location. The sites of location were: parietal peritoneum, serous surface of the uterus and wall of the uterine tube. The size of the nodules was 5 to 10 mm. Histologically, the lesions were hypocellular fibrotic nodules with a variable amount of neutrophils and amorphous eosinophilic material in the center, harbouring eggs of the parasite and remnants of pinworm cuticle. All three lesions were asymptomatic, only being discovered incidentally during the operations for unrelated conditions. Their peroperative recovery by a surgeon did not alter the course of surgery. These findings document the ability of pinworms to migrate into the abdominal cavity via the female genital tract.
Keywords: náhodný nález; Uterus; Female; vejcovody; dospělí; Adult; Peritoneum; uterus; peritoneum; Humans; ženské pohlaví; Oxyuriasis; lidé; Fallopian Tubes; Incidental Findings; oxyuriáza